2008
DOI: 10.1159/000122602
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Hepatic Fibrosis Using Serum Fibrotic Markers, Transient Elastography (FibroScan) and Real-Time Tissue Elastography

Abstract: Objective: The aim of this study was to investigate the accuracy of noninvasive tests, e.g. serum fibrotic markers, transient elastography and real-time tissue elastography, in the diagnosis of hepatic fibrosis, and to determine whether they can replace liver biopsy. Methods: 119 patients with chronic liver disease were included in this study. Serum fibrotic markers including hyaluronic acid, type IV collagen, type IV collagen 7S domain and type III procollagen-N-peptide were measured. Aspartate aminotransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 53 publications
5
66
0
4
Order By: Relevance
“…Comparing RTE with TE, similar results were found for the detection of significant fibrosis (≥F2), area under the curve (AUC) was 0.75 for ES and 0.75-0.84 for TE [1,[7][8][9]. Se -sensibility; NPV -negative predictive value; AUC -area under the curve; F -fibrosis stage [10], in a study involving 125 patients with viral hepatitis of various etiologies. To assess the stiffness of the left liver lobe, the probe was placed in the epigastrium, and for the right liver lobe, the probe was placed in a right intercostal space.…”
Section: Fujimoto Et Almentioning
confidence: 53%
“…Comparing RTE with TE, similar results were found for the detection of significant fibrosis (≥F2), area under the curve (AUC) was 0.75 for ES and 0.75-0.84 for TE [1,[7][8][9]. Se -sensibility; NPV -negative predictive value; AUC -area under the curve; F -fibrosis stage [10], in a study involving 125 patients with viral hepatitis of various etiologies. To assess the stiffness of the left liver lobe, the probe was placed in the epigastrium, and for the right liver lobe, the probe was placed in a right intercostal space.…”
Section: Fujimoto Et Almentioning
confidence: 53%
“…Some authors have reported that mean strain values inversely correlated with liver stiffness and fibrosis in patients with CHC. On the other hand, the standard deviation of values of strain, the percentage of area of low strain and its complexity were positively correlated with liver stiffness and fibrosis [126].…”
Section: Evaluation Methodsmentioning
confidence: 95%
“…Different scores for semi-quantitative interpretation of SE have been proposed: the German Elasticity Score [121], the Japanese Elasticity Score [126] and the LF Index [127]. The LF Index (an algorithm based of nine features evaluated directly by software) is the only one recommended by the manufacturer [32].…”
Section: Scoresmentioning
confidence: 99%
“…188 New reliability criteria for transient elastography have indicated that determinations of hepatic fibrosis are reliable (74%) or very reliable (17%) in 91% of assessments and poorly reliable in 9%. 189 Transient elastography has been similar to 190,191 or better than 192 APRI as a predictor of cirrhosis, and its performance has been similar to 190 (or possibly lower 193 than), the FibroTest for diagnosing the stages of fibrosis in chronic hepatitis C ( Table 3). The combination of ELF with transient elastography has increased the negative and positive predictive values of each test alone for the diagnosis of hepatic fibrosis stage ≥2 and cirrhosis.…”
Section: Transient Elastographymentioning
confidence: 96%
“…161 Comparative trials: Same or better than APRI for cirrhosis [191][192][193] Same or worse than FibroTest by stages 191,194 FibroTest and FibroScan match liver biopsy 191 Confirmed effective by four meta-analyses 179,[195][196][197] Predictive of 5-year survival in chronic HCV 162 Many non-fibrotic factors affect liver stiffness [201][202][203][204] Tested in chronic HCV 189,191,194 , HBV 198,199 Real-time elastography Measures echo displacement before and after liver compression and reconstructs strain field as reflective of tissue elasticity Spleen stiffness correlates with varices 217,218 Many non-fibrotic factors affect liver stiffness 221,225 Tested in diverse chronic liver diseases 209 APRI, aspartate aminotransferase/platelet ratio index; ARFI, acoustic radiation force impulse imaging; AST, serum aspartate aminotransferase level; HBV, hepatitis B virus; HCV, hepatitis C virus.…”
Section: Transient Elastographymentioning
confidence: 99%